Kewarisan Istimewa Gharawain Pasal 178 Ayat (2) Kompilasi Hukum Islam Dalam Isu Kesetaraan Perspektif Feminis Legal Teori - Ahmad Faza Bin Naja (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Article 173 of the Compilation of Islamic Law is an article regarding inheritance. This article contains the issue of